Low Temperature Plasticity of Ultrafine‐Grained AE42 and AZ31 Magnesium Alloys1. Issue 5 (17th December 2012) - Shumilin, Sergii Eduardovich; Janecek, Milos; Isaev, Nikolai Vasilievich; Minarik, Peter; Kral, Robert
Abstract The low temperature peculiarities of plastic deformation of AZ31 and AE42 magnesium alloys processed by equal‐channel angular pressing (ECAP) were studied in temperature range 0.5–293 K. At 4.2 K and lower, the stress–strain curves become serrated with the jerk stress frequency and amplitude sensitive to the flow stress, temperature and processing history. The yield stress of the samples before and after ECAP is determined by both the grain size refinement and basal texture evolution. The slope of the temperature dependencies of the yield stress is typical for the thermally activated interaction of dislocations with a spectrum of local obstacles. The activation of the dynamic recovery is responsible for the decrease of the work hardening rate of the samples (i) with a temperature increase and (ii) after ECAP.